Scientific And Methodological Approaches To Teaching The Russian Language In High School In The Context Of Educational Digitalization - Ibragimova Feruza Rustamovna (Zien Journals, 2025)
the article examines scientific and methodological approaches to teaching the Russian language in high school within the context of the digitalization of education. It analyzes modern pedagogical technologies, digital tools, and platforms used to enhance the effectiveness of teaching and learning. Special attention is given to the integration of traditional methods with digital resources, as well as to the development of cross-disciplinary competencies, media literacy, and critical thinking among students. The author emphasizes the need to rethink the teacher’s role in the digital educational environment and to update methodological practices in light of new realities. The conclusions and recommendations presented may be useful for teachers, educational methodologists, and developers of digital educational programs.
Keywords: Russian language; high school; educational digitalization